Planar polarity of root hair positioning in Arabidopsis. (22nd January 2007) - Fischer, U.; Ikeda, Y.; Grebe, M.
Abstract : The co-ordinated polarity of cells within the plane of a single tissue layer (planar polarity) is intensively studied in animal epithelia but has only recently been systematically analysed in plants. The polar positioning of hairs in the root epidermis of Arabidopsis thaliana provides an easily accessible system for the functional dissection of a plant-specific planar polarity. Recently, mutants originally isolated in genetic screens for defects in root hair morphogenesis and changes in the sensitivity to or the production of the plant hormones auxin and ethylene have identified players that contribute to polar root hair placement. Here, we summarize and discuss recent progress in research on polar root hair positioning from studies in Arabidopsis .